1999
DOI: 10.1016/s0304-3959(98)00202-4
|View full text |Cite
|
Sign up to set email alerts
|

Hemisensory impairment in patients with complex regional pain syndrome

Abstract: The purpose of the present study was to investigate the extent and quality of sensory impairment and their relation to pain characteristics and movement disorders in patients suffering from complex regional pain syndrome (CRPS) type I. Neurological testing was performed independently by two examiners in 24 patients with CRPS type I. In eight patients (33%), a hemisensory impairment with decreased temperature and pinprick sensation ipsilateral to the limb affected by CRPS could be observed. In four patients (17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(96 citation statements)
references
References 16 publications
4
80
1
11
Order By: Relevance
“…A similar dissociation involving persistence of deep-pressure pain and loss of cutaneous sensation was observed recently in patients with central post-stroke pain following sub-cortical and parietal or frontal lobe infarcts (Mailis and Bennett, 2002), indicating that painful cutaneous and deep-pressure sensations are processed by different central mechanisms. Rommel et al (1999; detected generalized sensory deficits to light touch and thermal stimulation on the side of the body ipsilateral to the affected limb in about one-third of CRPS patients, but did not investigate pressure-pain sensitivity in the forehead. In line with these observations, we found that sensitivity to sharp stimulation, cold and heat-pain was diminished in the ipsilateral forehead of patients with diminished touch sensitivity in the affected limb.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A similar dissociation involving persistence of deep-pressure pain and loss of cutaneous sensation was observed recently in patients with central post-stroke pain following sub-cortical and parietal or frontal lobe infarcts (Mailis and Bennett, 2002), indicating that painful cutaneous and deep-pressure sensations are processed by different central mechanisms. Rommel et al (1999; detected generalized sensory deficits to light touch and thermal stimulation on the side of the body ipsilateral to the affected limb in about one-third of CRPS patients, but did not investigate pressure-pain sensitivity in the forehead. In line with these observations, we found that sensitivity to sharp stimulation, cold and heat-pain was diminished in the ipsilateral forehead of patients with diminished touch sensitivity in the affected limb.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, pain and other sensory disturbances persist and may spread to other parts of the affected limb and even to other limbs (Maleki et al, 2000). Furthermore, in about one-third of patients, the pain is accompanied by loss of light tactile sensations in the affected limb and elsewhere on that side of the body (Thimineur et al, 1998;Rommel et al, 1999;Rommel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ribbers et al [35] found that those with left hand CRPS also had motor impairments such as deficits in the execution of movements of the unaffected right hand. Sensory disturbances including impaired pinprick and temperature sensations were found by Rommel et al [36] in the unaffected limb ipsilateral to the CRPS affected limb in over a third of cases. Conversely, by using a mirror to create a visual illusion, CRPS symptoms have been generated on the affected side when only the unaffected side was touched [2].…”
Section: Bilateral Impairment In a Unilateral Conditionmentioning
confidence: 86%
“…11 For example, Wasner et al 12 have shown that thermoregulatory reflexes are disturbed in the distal parts of the affected extremity in patients with CRPS I, which has been attributed to central changes reflected by alterations in the activity in cutaneous vasoconstrictor neurons. Besides, Rommel et al 13,14 have demonstrated that up to 50% of patients with chronic CRPS I develop hypoesthesia on the entire half of the body or in the upper quadrant ipsilateral to the affected limb. The anatomic distribution of these changes suggests that they might be due to changes in central processing of tactile stimuli, presumably at a thalamic or cortical level.…”
mentioning
confidence: 99%